Experimental Melting of Hydrothermally Altered Rocks: Constraints for the Generation of Low-δ18O Rhyolites in the Central Snake River Plain. (3rd December 2019) - Troch, Juliana; Ellis, Ben S; Harris, Chris; Ulmer, Peter; Bouvier, Anne-Sophie; Bachmann, Olivier
Abstract: Quantifying the relative contributions of crustal versus mantle-derived melt is important for understanding how silicic magmas are generated, stored, and interact with country rock in trans-crustal magmatic systems. Low-δ 18 O rhyolitic ignimbrites and lavas erupted during Miocene volcanic activity in the central Snake River Plain (14–6 Ma) have been inferred to be the result of large-scale partial or bulk melting of pre-existing hydrothermally altered lithologies of the Idaho batholith and Challis volcanic field. In this study, we assess the melting behaviour of heterogeneously altered source materials via partial melting experiments over a range of run times at conditions of 750–1000°C and 1–2 kbar, and apply our observations to current models for the petrogenesis of low-δ 18 O rhyolites along the Yellowstone hotspot track. Partial melt produced in the experiments inherits the bulk oxygen isotope composition from hydrothermally altered peraluminous source materials independent of the melt fraction, excluding the possibility for preferential, disequilibrium melting of 18 O-depleted mineral phases during incipient melting. We propose a new model to explain the generation of low-δ 18 O rhyolites in the central Snake River Plain, whereby mantle-derived magmas assimilate ∼30–40% of crustal material that was hydrothermally altered at high temperatures in two stages: (1) a preceding episode of hydrothermal alteration during intrusion of Eocene plutons ('pre-existing source'); (2) syn-magmatic hydrothermal alteration within a nested caldera complex. During assimilation, dilution of peraluminous crustal lithologies with mantle-derived magma maintains the metaluminous character of rhyolites erupted along the Yellowstone hotspot track. These results link previous models favouring melting of either pre-existing or syn-magmatically altered lithologies for the generation of low-δ 18 O rhyolites along the Yellowstone hotspot track and provide direct experimental observation of the chemical processes occurring during assimilation processes in magmatic environments.